2014
DOI: 10.1111/aab.12160
|View full text |Cite
|
Sign up to set email alerts
|

Seed biopriming with drought tolerant isolates ofTrichoderma harzianumpromote growth and drought tolerance inTriticum aestivum

Abstract: Green house study was aimed to investigate the effect of seed biopriming with drought tolerant isolates of Trichoderma harzianum, viz. Th 56, 69, 75, 82 and 89 on growth of wheat under drought stress and to explore the mechanism underlying plant water stress resilience in response to Trichoderma inoculation. Measurements of relative water content, osmotic potential, osmotic adjustment, leaf gas exchange, chlorophyll fluorescence and membrane stability index were performed. In addition, analysis of the phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 41 publications
6
25
0
4
Order By: Relevance
“…However, the mechanism of action remains unclear. Our results agree with an earlier study by Shukla, Awasthi, Rawat, and Kumar () who reported endophyte Trichoderma harzianum treated wheat F 1 plants produced less (13%–27%) H 2 O 2 compared to untreated (60%) wheat plants under drought stress. To the best of our knowledge, this is the first study to address this question in F2 chickpeas.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mechanism of action remains unclear. Our results agree with an earlier study by Shukla, Awasthi, Rawat, and Kumar () who reported endophyte Trichoderma harzianum treated wheat F 1 plants produced less (13%–27%) H 2 O 2 compared to untreated (60%) wheat plants under drought stress. To the best of our knowledge, this is the first study to address this question in F2 chickpeas.…”
Section: Discussionsupporting
confidence: 93%
“…The differential response of the different wheat cultivars to drought or normal irrigation conditions might have been due to their differential genetic potential to the prevalent conditions. Previous studies have shown that severe water stress from seedling to maturity reduced gas exchange activities and grain yield components in wheat, especially photosynthesis, stomatal conductance, productive tillers per unit area, number of grains per spike and 1000-grain weight (Ahmed et al 2007;Kilic & Yagbasanlar 2010;Nouri-Ganbalani et al 2009;Shukla et al 2015). However, it is shown that among the cultivars, Faisalabad-2008 maintained its superior performance and produced maximum yield under drought conditions.…”
Section: Effect On Grain Quality Parametersmentioning
confidence: 98%
“…This might have showed that drought stress has a direct impact on the photosynthetic activities by disrupting all major components due to stomatal closure that reduced CO 2 uptake under drought conditions. Early reports of photosynthesis include carbon reduction cycle, thylakoid electron transport, stomatal control of the CO 2 supply and disturbance of water balance (Shukla et al 2015;Vandoorne et al 2012). In fluctuating environmental conditions or environmental stress, stomatal and photosynthetic responses of plants differ especially under changing light and temperature conditions which lag in stomatal behavior and limit photosynthetic activity (Lawson et al 2011;Lawson & Blatt 2014).…”
Section: Effect On Grain Quality Parametersmentioning
confidence: 99%
“…This might be due to stomotal closure at early stage of herbicide spray that reduced CO 2 uptake under herbicide application. Early reports revealed that herbicides has a direct impact on photosynthetic activity by disrupting all major components of photosynthesis including carbon reduction cycle, thylakoid electron transport, stomatal control of the CO 2 supply and cholorophyll activity (Naseer-ud-Din et al, 2011;Vandoorne et al, 2012;Shukla et al, 2015). Different post-emergence herbicides has been used to control weeds but it is documented that application of post-emergence herbicide with adjuvants was found to be more effective in controlling the weeds (Naseer-ud-Din et al, 2011).…”
Section: T 1 T 2 T 5 T 3 T 4 T 6 T 7 T 8 T 9 T 10mentioning
confidence: 99%